1990
DOI: 10.1159/000181561
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Insulin-Like Growth Factor-I and Its Binding Protein in Polycystic Ovary Syndrome

Abstract: Patients with polycystic ovary syndrome (PCOS) had significantly higher levels of total insulin-like growth factor (IGF-I) than those in age- and weight-matched controls (PCOS, 230 ± 21 ng/ml; control, 180 ± 16 ng/ml; mean ± SE, p < 0.05) as well as free IGF-I (PCOS, 3.8 ± 0.2 ng/ml; control, 3.0 ± 0.2 ng/ml; p < 0.05). These elevated levels of IGF-I were correlated slightly with levels of LH and LH/FSH ratio (r = 0.171, p < 0.05 and r = 0.239, p < 0.01, respectively). Elevated fasting levels of insulin and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 32 publications
(39 reference statements)
3
25
0
Order By: Relevance
“…Potential contributors to excessive growth of theca-interstitial tissues in PCOS include insulin, insulin-like growth factor 1 (IGF1), and moderate oxidative stress. Indeed, PCOS is associated with hyperinsulinemia, elevated free IGF1, and increased oxidative stress [2][3][4][5][6][7][8]. Our previous in vitro studies [9][10][11] have demonstrated that insulin, IGF1, and moderate oxidative stress (such as that induced by hypoxanthine-xanthine oxidase) stimulate proliferation of rat theca-interstitial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Potential contributors to excessive growth of theca-interstitial tissues in PCOS include insulin, insulin-like growth factor 1 (IGF1), and moderate oxidative stress. Indeed, PCOS is associated with hyperinsulinemia, elevated free IGF1, and increased oxidative stress [2][3][4][5][6][7][8]. Our previous in vitro studies [9][10][11] have demonstrated that insulin, IGF1, and moderate oxidative stress (such as that induced by hypoxanthine-xanthine oxidase) stimulate proliferation of rat theca-interstitial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive growth of ovarian mesenchyme may also be due to a synergy between activin with insulin and IGF-I. Women with PCOS have typically significant hyperinsulinemia and elevated, free, bioavailable IGF-I [44][45][46][47]. In these patients, insulin and IGF-I may excessively amplify the proliferative actions of activin.…”
Section: Discussionmentioning
confidence: 99%
“…The most important regulator of cir culating low-molecular-weight IGF-binding protein con centrations is insulin [12,29]. It is therefore of interest that reduced serum concentrations of a low-molecularweight IGF-binding protein have recently been demon strated in PCO [ 13,14]. IGF-I-binding protein concentra tions were significantly lower in the obese PCO patients than in those who were non-obese [13,30], and fasting serum insulin concentrations correlated negatively with the IGF-I-binding protein concentrations [ 13,31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinsulinaemia has been shown to increase ovar ian androgen production by direct stimulation of gonadal steroidogenesis and/or gonadotropin secretion [6,7], The hormone could also, as recently suggested, control the concentration of insulin-like growth factor-1 (IGF-I), which in turn may regulate ovarian function [8][9][10], Insu lin-induced alterations in IGF-1 levels could also result from direct stimulation of hepatic production [11] or from a reduction of low-molecular-weight IGF-binding protein levels [ 12], It is therefore of interest that increased IGF-I concentration was recently reported in women with PCO, in association with reduced IGF-binding protein [13,14], This supports the suggestion that PCO results from a primary abnormality in the growth hormone (GH)/IGF axis [ 15],…”
Section: Introductionmentioning
confidence: 99%